Postmodernism and the en-gendering of Marcel Duchamp - Jones, Amelia 1961- (Cambridge Univ. Press, 1994)
Focusing primarily on American texts that construct Marcel Duchamp as the origin of postmodern art, Amelia Jones contends that Duchamp, through his readymades, has paradoxically served in a paternal role for post-1960s American artists, critics, and art historians, who have attempted to construct a new tradition of artistic practice that counters the masculinist ideologies of abstract expressionism and Greenbergian modernism. Adapting feminist, psychoanalytic, and Derridean conceptions of interpretation as an exchange of sexual identities, Jones offers highly charged readings that focus on the eroticism of Duchamp's works and on his theories of artistic production. She reconstructs Duchamp as an indeterminably gendered author whose gift to postmodernism might best be viewed in terms of the potential of his works and self-productions to destructure conventional notions of sexual difference and subjectivity
Keywords: Duchamp, Marcel <1887-1968>; Duchamp, Marcel <1887-1968> - Critique et interprétation; Duchamp, Marcel <1887-1968> -- Criticism and interpretation; Duchamp, Marcel -- 1887-1968; Geschichte 1900-2000; Beeldende kunsten; Critique d'art féministe - États-Unis; Kunsttheorie; Postmodernisme; Sekseverschillen; Geschlechtsunterschied; Kunst; Postmoderne; Feminist art criticism -- United States; Kunstbetrachtung; Kunstkritik; Frauenkunst; Kunstsoziologie; Geschlechterforschung; USA